Zakaz korzystania z niektórych wyrobów pirotechnicznych jako instrument ochrony środowiska i dobrostanu zwierząt – analiza rozwiązań prawnych na tle postulatów społecznych - Januszczyk, Maria; Kaźmierczyk, Aneta; Łabędzka, Marzena; Zawistowska-Dąbrowska, Milena (PRAWO i WIĘŹ, 2025)
The issues of animal and environmental protection have increasingly been raised in the public debate, which is reflected in growing public support for restricting or prohibiting the use of certain pyrotechnic products. This phenomenon seems to go beyond seasonal emotions and is part of a broader discussion on changing the law in accordance with new ethical and environmental standards. The aim of this article is to analyse the current and proposed legislation on restricting the general use of F2 and F3 class fireworks in the light of interpretative directives arising from the Animal Welfare Act